Midnight on the moon : the graphic novel - Osborne, Mary Pope; Laird, Jenny, 1969- (Mary Pope Osborne's Magic tree house (Graphic novel series), 2025)
The magic treehouse takes Jack and Annie to a moon base in the future where they continue to search for the fourth thing they need to free their friend Morgan from the magician's spell.